PEMBELAJARAN PAI BERBASIS PROYEK (PROJECT-BASED LEARNING) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN KETERAMPILAN SOSIAL-EMOSIONAL SISWA MTs KECAMATAN BUNGO: EKSPERIMEN KUASI - Baili; Paradila; Mabruri; Andryadi; Kurniawan, Sugeng; Sabli, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT Islamic Religious Education (PAI) at Islamic junior high schools (MTs) still tends to focus on normative knowledge transmission and memorization, resulting in suboptimal development of students' critical thinking and social-emotional learning (SEL) skills. This study aims to examine the effectiveness of Project-Based Learning (PjBL) in improving both variables among MTs students in Bungo District, Jambi. The research employed a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 64 eighth-grade students selected through cluster random sampling from two MTs, divided into an experimental group (n=32) and a control group (n=32). Instruments included a critical thinking test (25 items, α=0.88) and an SEL questionnaire (24 items, α=0.91). Data were analyzed using prerequisite tests, MANOVA, paired and independent sample t-tests, Normalized Gain (N-gain), and Cohen’s d effect size. Results indicate that (1) PjBL significantly improves critical thinking skills (p=0.000; N-gain=0.58; d=1.21), (2) PjBL significantly improves SEL (p=0.000; N-gain=0.52; d=1.32), and (3) simultaneously, PjBL explains significant variance in both dependent variables (Wilks’ Λ=0.412; F=34.67; p=0.000). Findings confirm that PjBL in PAI not only activates higher-order cognition through contextual problem-solving but also facilitates the development of self-regulation, empathy, collaboration, and responsible decision-making. The study recommends integrating structured PjBL into PAI Learning Modules, strengthening teachers' facilitative competencies, and supporting policies that provide collaboration time and authentic assessment. Results contribute to the development of 21st-century PAI pedagogy aligned with the Merdeka Curriculum and Pancasila Student Profile.